2018
DOI: 10.1002/dneu.22640
|View full text |Cite
|
Sign up to set email alerts
|

Spastin Interacts with CRMP5 to Promote Neurite Outgrowth by Controlling the Microtubule Dynamics

Abstract: Changing the microtubule dynamics is sufficient to alter the axon and dendrite specification and development. Spastin participates in the growth and regeneration of neurites by severing microtubules into small segments, and collapsin response mediator protein 5 (CRMP5) provides structural support and serves as a track for cargo transport by promoting microtubule polymerization. Nevertheless, how spastin and CRMP5 cooperate to regulate neurite outgrowth by controlling the microtubule dynamics needs to be elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 38 publications
4
43
0
Order By: Relevance
“…Microtubule dynamics entail a balance of microtubule stabilization and destabilization, regulated by various factors, including microtubule-severing proteins [9,32]. Previous studies have demonstrated that the upregulation of microtubule-severing proteins favors neurite outgrowth [35,49,50], so our further experiments mainly aimed to answer the question of whether RhoA regulates neurite outgrowth via the regulation of the expression of microtubule-severing proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microtubule dynamics entail a balance of microtubule stabilization and destabilization, regulated by various factors, including microtubule-severing proteins [9,32]. Previous studies have demonstrated that the upregulation of microtubule-severing proteins favors neurite outgrowth [35,49,50], so our further experiments mainly aimed to answer the question of whether RhoA regulates neurite outgrowth via the regulation of the expression of microtubule-severing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Short and free microtubules and the dynamic remodeling of microtubules are thought to be important for growth cone migration and neurite outgrowth [35,53]. Several studies have revealed that spastin plays a key role in the growth of neurites [35,50,54]. Katanin is a heterodimer, consisting of the p60 enzyme subunit (encoded by the KATNA1 gene) and the p80 enzyme subunit (encoded by the KATNB1 gene); p60 is involved in the actual severing, whereas the p80 subunit has no severing activity, acting instead to regulate the severing activity of p60-katanin [52].…”
Section: Discussionmentioning
confidence: 99%
“…Spastin is a microtubule-cleaving protein involved in a variety of functional regulation processes, including microtubule dynamics [9,10], membrane transport [11], Cytokinesis [12], neurite growth [13,14] and axonal transport [15], etc. Spastin plays an important role in neuronal development and participates in the process of neurite outgrowth and formation of lateral branch, which may be related to the regulation of microtubules [16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to several tubulin genes, four of the five Crmp genes were up-regulated in TCDD-exposed hippocampi. CRMP proteins can positively and negatively regulate microtubule polymerization dynamics through interaction with tubulins, allowing them to regulate neurite outgrowth (Fukata et al 2002;Uchida et al 2005;Yoshimura et al 2005;Aylsworth et al 2009;Brot et al 2010;Takaya et al 2017;Ji et al 2018). In addition, many of the genes involved in the axon guidance have been described to have vital roles in regulation of dendritic arborization (Ledda and Paratcha 2017).…”
Section: Transcriptional Outcomes Of Gestational Low-dose Tcdd Exposurementioning
confidence: 99%